2020
DOI: 10.1634/theoncologist.2020-0440
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Single-Arm, Open-Label, Bayesian Adaptive Efficacy and Safety Study of PBI-05204 in Patients with Stage IV Metastatic Pancreatic Adenocarcinoma

Abstract: • This trial evaluating a novel plant extract, PBI-05204, did not meet its primary endpoint of overall survival but did show signals of efficacy in heavily pretreated mPDA. • PBI-05204 was generally well tolerated, with the most common side effects related to treatment being vomiting (23.7%), nausea (18.4%), decreased appetite (18.4%), and diarrhea (15.8%). • Additional trials are needed to explore the role of PBI-05204 in cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Previously we reported that oleandrin has a capability of crossing the blood brain barrier and selectively inhibits human malignant cell proliferation but not that of normal cells due to the ability of oleandrin to interact with a unique isoform of Na, K-ATPase that is preferentially expressed in malignant tissue (Ni et al, 2002;Lin et al, 2008;Yang et al, 2009). Given that PBI-05204, a defined extract of Nerium oleander containing oleandrin, has multiple mechanisms for inhibiting malignant cell growth and proliferation and has been through both phase I (Hong et al, 2014) and phase II (Roth et al, 2020) clinical trials in cancer patients, we sought to examine the potential role of this botanical drug in the treatment of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported that oleandrin has a capability of crossing the blood brain barrier and selectively inhibits human malignant cell proliferation but not that of normal cells due to the ability of oleandrin to interact with a unique isoform of Na, K-ATPase that is preferentially expressed in malignant tissue (Ni et al, 2002;Lin et al, 2008;Yang et al, 2009). Given that PBI-05204, a defined extract of Nerium oleander containing oleandrin, has multiple mechanisms for inhibiting malignant cell growth and proliferation and has been through both phase I (Hong et al, 2014) and phase II (Roth et al, 2020) clinical trials in cancer patients, we sought to examine the potential role of this botanical drug in the treatment of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…86 PBI-05204, a carefully defined extract of N. oleander containing a controlled concentration of oleandrin was evaluated in both Phase I and Phase II clinical trials for treatment of advanced cancer patients. 14,15 Those studies showed that oleandrin, the active principle ingredient, and other compounds in the extract could be safely administered to humans without serious adverse effects. The Swiss physician Paracelsus has been quoted as saying that "The dose makes the poison".…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of oleander extracts with carefully defined concentrations of oleandrin have shown promise that this cardenolide, at least when included in the PBI-05204 extract, can be safely administered to patients with therapeutic intent. 14,15 At the present time, the specific mechanism(s) by which oleandrin, or extracts containing this molecule, provide antiviral activity against specific viruses is not known; however, multiple mechanisms of the antiviral activity of oleandrin have been suggested and deserve further inquiry. For example, in addition to targeting HIV-1, 17 the findings by Hutchison et al, 19 that oleandrin and a N. oleander phytoextract can inhibit the infectivity and Env-dependent intercellular transmission of HTLV-1 across the VS allude to the therapeutic potential of oleandrin as a broad-spectrum antiviral to combat infections by enveloped viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use of oleandrin and extracts of the oleander ( N. oleander ) plant containing oleandrin, as effective therapeutics that range from cosmetic treatment of skincare problems [13] to the treatment of cancer [14] , [15] , [16] . Oleandrin, a unique lipid-soluble cardiac glycoside obtained solely from Nerium oleander , has been recognized as the active principal ingredient in PBI-05204 used in Phase I and Phase II clinical trials of patients with cancer [17] , [18] . These trials defined the pharmacokinetics of oleandrin and demonstrated that extracts containing this molecule, along with other components found in the extract, can be administered safely as an oral drug to patients without significant adverse events.…”
Section: Introductionmentioning
confidence: 99%